Penerapan Model Pembelajaran Kooperatif Tipe Talking Stick Berbantu Kartu Bergambar Untuk Meningkatkan Hasil Belajar Pendidikan Pancasila - Juliana Juliana; Abdulah; Randi Eka Putra (JURNAL KEILMUAN TEKNOLOGI DAN PENDIDIKAN TERPADU, 2025)
This research is based on the academic achievement of Pancasila Education subjects of third grade students at SDN 130/II Pasir Putih which is still less than optimal. due to the lack of active student participation and the dominance of lecture methods that cause students to be passive. Research This research aims to improve learning activities and student academic achievement by implementing certain learning strategies. Cooperative learning model Talking Stick type assisted by picture cards. This research method applies a two-round Classroom Action Research (CAR) learning method that includes the preparation, implementation, observation, and evaluation phases. The research subjects involved 15 third grade students. Research data was obtained through the process of collecting and observing as well as evaluation questions. The research findings show significant progress in the implementation of learning starting from 66.67% in the first cycle, while in the second cycle it reached 94.44% with a very good classification. Student involvement increased classically with 86.67% of students achieving KKTP. The Cooperative learning model Talking Stick type assisted by picture cards has been proven effective in maximizing the quality of the process and learning outcomes of Pancasila Education.